2022
DOI: 10.3758/s13421-022-01363-6
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific auditory distraction in serial recall and mental arithmetic

Abstract: Previous studies suggest that task-irrelevant changing-state sound interferes specifically with the processing of serial order information in the focal task (e.g., serial recall from short-term memory), whereas a deviant sound in the auditory background is supposed to divert central attention, thus producing distraction in various types of cognitive tasks. Much of the evidence for this distinction rests on the observed dissociations in auditory distraction between serial and non-serial short-term memory tasks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 91 publications
2
8
3
Order By: Relevance
“…We should note that Kattner et al (2022) did not observe the deviation effect not only in the mental arithmetic task but even in the serial recall task, which is inconsistent with earlier studies (e.g., Hughes et al,2007;Hughes, Hurlstone, Marsh, Jones, Vachon,2013;Vachon et al,2017;Marsh, Campbell, Vachon, Taylor, Hughes, 2020). They stated the possibility that some procedural aspects of their experiments led to the lack of the deviation effect.…”
Section: Introductioncontrasting
confidence: 83%
See 3 more Smart Citations
“…We should note that Kattner et al (2022) did not observe the deviation effect not only in the mental arithmetic task but even in the serial recall task, which is inconsistent with earlier studies (e.g., Hughes et al,2007;Hughes, Hurlstone, Marsh, Jones, Vachon,2013;Vachon et al,2017;Marsh, Campbell, Vachon, Taylor, Hughes, 2020). They stated the possibility that some procedural aspects of their experiments led to the lack of the deviation effect.…”
Section: Introductioncontrasting
confidence: 83%
“…Second, experiments 2 and 3 of their study were online experiments in which the experimental environment could not be fully controlled. Note that the changing-state effect was observed only in the serial recall task, as expected in Kattner et al (2022).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Concerning the former, it has consistently been shown that children’s language comprehension is more impaired than adults’ by noise and reverberation [ 10 , 11 , 12 , 13 ]. Concerning non-auditory tasks, findings are less consistent for complex academic tasks such as reading and numeracy [ 14 , 15 , 16 ] (for review, see [ 17 ], but reliable noise-induced performance decrements have been reported for children’s visual–verbal short-term memory [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%